Chemical composition, vitamins and minerals of a new cultivar of lychee (Litchi chinensis cv. Tailandes) grown in Brazil. (3rd October 2014) - Cabral, Thalita Azevedo; Cardoso, Leandro de Morais; Pinheiro-Sant'Ana, Helena Maria
Abstract : Introduction . Different cultivars of lychee are produced all around the world and to date no information has been published on the nutritional value of cv. Tailandes, which is a new lychee cultivar introduced into Brazil and other tropical countries. Our study performed a pioneering evaluation of the physical and chemical characteristics, carotenoids, vitamins, and minerals in pulp of fruit of this cultivar.Materials and methods . Titratable acidity was determined by volumetric neutralization, pH by potentiometry, soluble solids by refractometry, moisture by gravimetry after oven drying, ash by calcination in a muffle furnace, proteins by the micro-Kjeldahl method, dietary fibers by the gravimetric non-enzymatic method and lipids by gravimetry after extraction in ethyl ether. Vitamin C (ascorbic and dehydroascorbic acids) and carotenoids (a-carotene, b-carotene, b-cryptoxanthin and lycopene) were analyzed by high-performance liquid chromatography (HPLC) with diode array detection, vitamin E (a-, b-, g- and d-tocopherols and tocotrienols) was analyzed by HPLC with fluorescence detection, and fourteen minerals were analyzed by atomic absorption spectrometry in inductively coupled plasma.Results and discussion . The lychee cv. Tailandes showed high pulp yield (59.0%), moisture (80.7 mg×100 g–1) and dietary fiber (2.2 g×100 g–1), and a low total energy value (70.2 kcal×100 g–1). It presented no carotenoids, but was an excellent source of vitamin C (34.7 mg×100 g–1). The total vitamin E content was 117.0 g×100 g–1. Pulp of lychee cv. Tailandes was shown to be a source of iron (0.86 mg×100 g–1) and magnesium (12.90 mg×100 g–1), a good source of copper (0.12 mg×100 g–1) and an excellent source of potassium (1067.33 mg×100 g–1).Conclusion . The lychee cv. Tailandes showed high pulp yield and low total energy. The pulp is a source of dietary fiber, vitamin C, iron, magnesium, copper and potassium.